Management Effectiveness of Rinjani-Lombok Geopark on Geotourism Track - Ayu Puspa Kartika; Bambang Hari Wibisono (Built Environment Studies, 2020)
Managing the Geopark involves the integration between several aspects; conservation, education, and the sustainable community economic development. Multistakeholder is responsible for managing the Geopark. To make it effective, the stakeholders should work equally balanced. This study is aimed to evaluate the management effectiveness of Geopark in Geotourism track with specified theme. The method that was used in this study is descriptive quantitative approach, with the help of rating scale to analyze partial scoring and managing, as well as in each aspect and as a whole. This research was done at Rinjani-Lombok Geopark which focused on Geotourism track 2: the Ancient Volcanic Mountains Trail in Sembalun Valley and Geotourism Track 3: The Youngest Volcanic Mountain, Rinjani. The respondents were chosen by non-probability-sampling method, which is purposive sampling. It consists of Geopark management, government, locals, and tourists. As a result, it is shown that the management effectiveness is considered average, and also there are some imbalances found among the aspects mentioned. Educational aspect has the lowest efficiency, while the rests of the aspects are on average level. There are several indicators that influenced in educational aspect, and one of them is caused by the worst management.